THE DEVELOPMENT OF LAKUER PAINTING PRODUCT TO CRAFTS PRODUCT - Mubarat, Husni; Chanaldy, Rendi Sueztra; Yanto, Desri (Institut Seni Indonesia Padangpanjang, 2019)
The community service with a scheme of community partnership program, was carried out with the Sanggar of Ganesha Art Group Palembang who was active in visual arts activities, particularly lakuer painting. Lakuer itself is one of the crafts in the city of Palembang that has local genius, aesthetic and unique value that is not owned by other regions, especially in Sumatra. The potential of lakuer painting which was developed together with the Sanggar Ganesha Art Group is the development of product design as a medium of lakuer painting, which was previously in the form of paintings with 2-dimensional fields developed into craft products in the shape of a square, cylinder or tube. The specific purpose of this service is to develop product designs from lakuer painting to craft products that can be mass produced, namely to increase the quantity and quality of products through technology transfer from manual work to machine work systems. Another aim is to conduct training on production management and financial management of Sanggar Ganesha Art Group in order to become a creative business that has economic and professional value. It apllied demonstration method in the form of training and workshops on design development and production management directly with a work system that is supported by machine technology and financial management. The implementation of the service also applied promotional methods through online media in order to increase product sales.